The Effect of Uric Acid Levels on Bone Metabolism in Postmenopausal Women - Mustafa Şahin; Okan Dikker; Sevgi Atar (Galenos Yayinevi, 2019)
Objective:The decrease in estrogen levels leads to oxidative stress by accumulating reactive oxygen species in the cell and suppressing the antioxidant defense system. Thus, the activity of osteoclasts and bone resorption are stimulated. It is stated that uric acid may contribute to the bone mineral density (BMD) due to antioxidant specialty. In our study; we investigated the relationship among serum uric acid levels, BMD and other bone metabolic markers in women with the postmenopausal period. Materials and Methods: BMD and laboratory data (glucose, urea, creatinine, calcium, phosphorus, alkaline phosphatase, uric acid, parathyroid hormone, and 25-hydroxyvitamin D3 levels) of 141 postmenopausal women aged between 50 and 69 were evaluated. The participants were divided into three groups according to the t-score. These were; the patients with t-score <-2.5 were osteoporosis patient group, t-score between -2.5 and -1.0 were osteopenia patient group, and t-score >-1 were normal BMD group. Biochemical tests were measured by photometric method and hormone tests were measured by electrochemiluminescence method. Results:Uric acid levels were significantly higher in the osteopenia group than the normal BMD group (p=0.023). There was no statistically significant difference in uric acid levels between the osteoporosis-steopenia and the osteoporosis-normal BMD groups. No correlation was found between uric acid levels and BMD in all groups. While there was a negative correlation in uric acid levels between the postmenopausal osteopenia and the normal BMD groups (r=-0.423, p=0.016), there was no a significant difference between the osteoporosis and the normal BMD groups (p>0.05). Conclusion:As a result of our study, it is difficult to mention a clear relationship between uric acid and lumbar BMD in postmenopausal women. We believe that further studies are needed for solving the uric acid riddle and explaining the effect on bone metabolism. In addition, uric acid levels in patients with postmenopausal osteopenia should be examined in detail.